Perbandingan Tingkat Penerimaan Pajak Hotel Dan Pendapatan Asli Daerah (PAD) Di Daerah Kota Malang - Safitri, Dewi; Nabilqodarsa, Merindah Dwi (Jurnalku, 2024)
Regional Original Income (PAD) is often used as a comparison material between districts/cities in Indonesia. Not only the amount, but also the composition of the amount of regional income apart from balancing funds and other legal regional income is interesting to consider.studied. Generally, PAD revenues are dominated by local taxes. Unfortunately, the types of local taxes are too rigid, making it difficult for districts/cities to innovate in order to increase PAD. To increase PAD, the first step that is needed is to analyze the potential of each region. By using documentsthe output of the Malang City Government between 2018-2022 which is analyzed quantitatively, this paper finds the results that economic development has changed the regional potential. Hotel taxes are a source of income that has high potential as a source of income for the people in Malang City as a tourist. This study aims to determine and analyze hotel tax in Malang city based on the number of hotels, the number of hotel occupancy rates, and the number of tourists on hotel tax revenue in Malang city for the period 2018 – 2022. The method used in this research is descriptive analysis and multiple linear regression analysis. Descriptive analysis is to describe the picture research data consisting of the number of hotels, the number of hotel occupancy rates, and the number of tourists in Malang City from 2018-2022. Meanwhile, multiple linear analysis serves to prove the hypothesis of the effect of the number of hotels, the number hotel occupancy rate, and the number of tourists to hotel tax revenue in Malang City. The results of this study indicate that the number of hotels, the number of tourists and occupancy rates have a significant effect on hotel tax receipts